2002
DOI: 10.1093/glycob/12.3.229
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression, purification, and partial characterization of Saccharomyces cerevisiae processing alpha glucosidase I

Abstract: The gene encoding yeast processing alpha glucosidase I, CWH41, was overexpressed in Saccharomyces cerevisiae AH22, resulting in a 28-fold increase in expression of the soluble form of the enzyme. The soluble enzyme results from proteolytic cleavage between residues Ala 24 and Thr 25 of the transmembrane sequence of the membrane-bound form of the enzyme. This cleavage could be partially inhibited by addition of leupeptin and pepstatin during the enzyme isolation. The enzyme was purified to a final specific acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 25 publications
1
30
0
1
Order By: Relevance
“…The sample was eluted with a continuous gradient of 0-1 M NaCl in the same buffer. Protein elution (open symbols) and a-glucosidase activity (closed symbols) was assessed in each fraction 1998; Dhanawansa et al 2002;Faridmoayer and Scaman 2005). However, our observations are consistent with those reported for a-glucosidase I from pig and rat liver, which are more sensitive to NEM than DEPC (Romaniouk and Vijay 1997;Zeng and Elbein 1998).…”
Section: Biochemical Characterization Of Recombinant Cwh41 C-terminussupporting
confidence: 88%
“…The sample was eluted with a continuous gradient of 0-1 M NaCl in the same buffer. Protein elution (open symbols) and a-glucosidase activity (closed symbols) was assessed in each fraction 1998; Dhanawansa et al 2002;Faridmoayer and Scaman 2005). However, our observations are consistent with those reported for a-glucosidase I from pig and rat liver, which are more sensitive to NEM than DEPC (Romaniouk and Vijay 1997;Zeng and Elbein 1998).…”
Section: Biochemical Characterization Of Recombinant Cwh41 C-terminussupporting
confidence: 88%
“…Samples of SF (1) and the enzyme fraction obtained after the Mono Q step (2) were separated in 7% non-denaturing electrophoresis gels and the enzyme band was detected with MUaGlc as described in the text from C. albicans has a molecular weight of 45 kDa (Torre-Bouscoulet et al 2004). Also, the yeast soluble and membrane-bound a-glucosidase I exhibit monomeric structures of 89-98 and 93.8 kDa, respectively (Dhanawansa et al 2002), in contrast to the tetramer reported for mammalian forms of the enzyme (Hettkamp et al 1984;Shailubhai et al 1987). In yeast, mammals and other organisms, a-glucosidase II is a soluble ER-resident heterodimer consisting of a and b chains of 95-110 (GIIa) and 50-60 (GIIb) kDa, respectively.…”
Section: Resultsmentioning
confidence: 96%
“…There is no clear electrostatic or hydrophobic patch on this face of the protein to indicate interaction with the membrane. In previous overexpression studies of the full-length Cwh41p in S. cerevisiae, both the membrane-bound and a soluble truncated form were isolated, despite the presence of a range of protease inhibitors during purification (23). This evidence of proteolytic cleavage of the protein in its native host could indicate that a portion of Cwh41p is present and active in its soluble form in the endoplasmic reticulum, without being tethered to the membrane.…”
Section: Cwht1p Structural Features and Keymentioning
confidence: 99%
“…In all eukaryotic homologs tested, GluI is specific for this linkage, and the minimum cleavable substrate is glucotriose with ␣(132) and ␣(133) linkages as found in the native substrate (15, 19 -22). The glucose-␣(132)glucose disaccharide, kojibiose, inhibits GluI activity weakly (15,23). Interestingly, the only documented biological occurrence of this glucotriose is found in the eukaryotic N-glycosylation pathway; thus, the relationship between this enzyme and this substrate is unique in biology.…”
mentioning
confidence: 99%